Development and performance evaluation of a solar tunnel date dryer in Oman - Mohammad Ali Basunia; Hamid H. Al-Handali; Mohammed Issa Al-Belushi; Mohammad Shafiur Rahman; Osman Maghoub (Journal of Agricultural and Marine Sciences, 2012)
Taking into consideration the date harvesting and landholding capacities of the marginalized rural farmers in Oman, a 12 meter long and 2 meter wide tunnel was designed and constructed to dry about 180-200 kg of freshly harvested dates per batch. Half of the tunnel base was used as a flat plate air heating solar collector and the other half as a dryer. The drying air was forced from the collector region (South side) to the drying region (North side) of the half circled tunnel where the product is to be dried. The drying temperature could be easily raised by some 5-30 oC above the ambient temperature inside the tunnel at an air velocity of approximately 0.5 m/sec. The test was conducted with 190.2 kg freshly harvested dates with initial moisture content of 32.8% (wet-basis) to analyze the performance of the dryer. The dates were dried to a final average moisture content of 18.6% (wet-basis) within two days (20 hours). The results indicated that the drying was faster in a solar tunnel dryer than the natural open air sun drying. It was possible to reach the moisture content level for safe storage within less than two days (20 hrs) with a solar tunnel dryer and 5-7 days in open air natural sun drying. The improvement in the quality of dates in terms of color and brightness was distinctly recognized.